Microbiome of Seven Full-Scale Anaerobic Digestion Plants in South Korea: Effect of Feedstock and Operational Parameters - Michal Sposob; Hee-Sung Moon; Dongjin Lee; Yeo-Myeong Yun (Energies, 2021)
In this study, the microbiomes linked with the operational parameters in seven mesophilic full-scale AD plants mainly treating food waste (four plants) and sewage sludge (three plants) were analyzed. The results obtained indicated lower diversity and evenness of the microbial population in sludge digestion (SD) plants compared to food digestion (FD) plants. Candidatus Accumulibacter dominated (up to 42.1%) in SD plants due to microbial immigration from fed secondary sludge (up to 89%). Its potential activity in SD plants was correlated to H2 production, which was related to the dominance of hydrogenotrophic methanogens (Methanococcus). In FD plants, a balance between the hydrogenotrophic and methylotrophic pathways was found, while Flavobacterium and Levilinea played an important role during acidogenesis. Levilinea also expressed sensitivity to ammonia in FD plants. The substantial differences in hydraulic retention time (HRT), organic loading rate (OLR), and total ammonium nitrogen (TAN) among the studied FD plants did not influence the archaeal methane production pathway. In addition, the bacterial genera responsible for acetate production through syntrophy and homoacetogenesis (Smithella, Treponema) were present in all the plants studied.